ИССЛЕДОВАНИЯ КОМПОЗИЦИОННОГО СОСТАВА ТЕЛА ЮНЫХ ФУТБОЛИСТОВ 13-14 ЛЕТ - Исмагилов, Д.К. (SCIENCE and SOCIETY, 2022)
The data obtained by bio impedance analysis allows us to assess the state of fitness at the examination stage. The differences in each stage of the survey allows us to compare the data and thereby get an idea of the rationality of using the means of the educational and training process and nutrition.